2011
DOI: 10.1007/s12206-010-1229-z
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the performance of polymer electrolyte membrane fuel cells due to the variation in gas diffusion layer permeability

Abstract: Convective flow in the under-rib regions of gas diffusion layers (GDLs) is a non-negligible transport process that can enhance the performance of polymer electrolyte membrane fuel cells (PEMFCs) by facilitating efficient utilization of catalyst layers (CLs) in those regions. The permeability of GDLs has been recognized as a dominant factor influencing the intensity of the under-rib convection in PEMFCs. In this study, the correlation between the permeability of GDLs and the performance of PEMFCs was numericall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…One direction is to develop the under-rib mass transport. The roles of the under-rib mass transport were previously studied [2,[12][13][14][15][16][17][18][19][20][21][22]. It was reported that for a specified mass flow rate, the under rib convection is mainly affected by different factors such as the rib width, the pressure difference between the adjacent channels, and the diffusion layer permeability [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…One direction is to develop the under-rib mass transport. The roles of the under-rib mass transport were previously studied [2,[12][13][14][15][16][17][18][19][20][21][22]. It was reported that for a specified mass flow rate, the under rib convection is mainly affected by different factors such as the rib width, the pressure difference between the adjacent channels, and the diffusion layer permeability [9,23].…”
Section: Introductionmentioning
confidence: 99%